(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To find out association between Nasal polyposis and bronchial asthma. Methods: This was a cross sectional study which was carried out in the departments of Otolaryngology and Head-Neck surgery of Bangabondhu Sheikh Mujib Medical University and Dhaka Medical College Hospital during the period of February 2014 to July 2014. A Total 230 patients were selected according to selection criteria among which 30 subjects had nasal polyposis (designated as group A or cases) and 200 subjects had no nasal polyposis (designated as group B or control group). Results: In group (A), asthma was found in 30.0% cases. On the other hand, asthma was found in 2.5% of control group (B). The association of nasal polyposis with bronchial asthma was highly significant (p<.05). In both group 40.0% patients were within the 38-47 year’s age group. In case group, 80.0% patients had any sorts of allergic history on the other hand, only 15.0% patients had allergic history in control group. High eosinophil count was found 66.7% patients suffering from nasal polyposis with bronchial asthma and in comparison to patients suffering from nasal polyposis without bronchial asthma had high eosinophil count 42.85%. In group A High IgE level was found 66.7% patients suffering from nasal polyposis with bronchial asthma, on the other hand, 42.85% had IgE level among patients suffering from nasal polyposis without bronchial asthma. Conclusion: Patients with nasal polyposis and asthma are significantly associated. Both serum IgE and total circulating eosinophil count are significant associated with nasal polyposis and bronchial asthma. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 11-18